Controlled Auto-Ignition (CAI) combustion in a two-stroke cycle engine using hot burned gases - Abdul Aziz, Azhar (2013)
A new combustion concept, which is viewed increasingly as a probable solution to these issues is Controlled Auto-Ignition (CAI) Combustion. In such an engine, a homogeneous mixture of air, fuel and residual gases is compressed until auto-ignition occurs. Due to its significantly low temperature combustion, NOx will be dramatically reduced while the mixture will be under ultralean fuel-air condition, thus able to achieve high efficiency and low emission. In the case of twostroke engine, problem of poor combustion efficiency and excessive white smoke emission can be addressed by the incorporation some features that will ultimately convert a typical two-stroke engine into an efficient CAI engine demonstrating the best of both features. Due to its inherent high internal residual gas rate in partial load operation, the two-stroke engine has been the first application to benefit from the unconventional CAI combustion process. This paper will concisely discuss the utilization of hot burned gas for induction thus imposing a CAI combustion feature onto two-stroke cycle engine. Among the features incorporated are the increasing in the level of Exhaust gas Recirculation and cycle-by-cycle uniformity of the air-fuel ratio (AFR) supplied to cylinder, which will be crucial in creating a suitable temperature within the engine’s combustion chamber.